دور كتب الدراسات الاجتماعية والوطنية في السعودية في تعزيز الأمن الوطني والنظرة المستقبلية لهذا الدور: محافظة القريات إنموذجاً - العنزي، علي بشير; الكراسنة، سميح محمود محمد; القاعود، إبراهيم عبدالقادر أحمد (جامعة القدس المفتوحة, 2019)
هدفت هذه الدراسة إلى الكشف عن دور كتب الدراسات الاجتماعية والوطنية في السعودية في تعزيز الأمن الوطني والنظرة المستقبلية لهذا الدور "محافظة القريات أنموذجا". ولتحقيق أهداف الدراسة، تم إعداد استبانة مكونة من (33) فقرة موزعة على أربعة مجالات، كما تم إعداد تسعة أسئلة لمقابلة المعلمين، للكشف عن النظرة المستقبلية لدور كتب الدراسات الاجتماعية والوطنية في تعزيز الأمن الوطني في محافظة القريات. تكونت عينة الدراسة من (145) معلماً من معلمي الدراسات الاجتماعية في محافظة القريات، تم اختيارهم بالطريقة القصدية. أظهرت نتائج الدراسة أن دور كتب الدراسات الاجتماعية والوطنية في تعزيز الأمن الوطني من وجهة نظر المعلمين، جاء بدرجة مرتفعة على الأداة ككل وفي جميع المجالات، كما أظهرت النتائج ندرة وجود فروق في وجهة نظر المعلمين حول دور كتب الدراسات الاجتماعية والوطنية في تعزيز الأمن الوطني، تعزى لمتغيري المؤهل العلمي والخدمة العملية، كما بينت النتائج أن النظرة المستقبلية لدور كتب الدراسات الاجتماعية والوطنية في تعزيز الأمن الوطني تكمن في عدة محاور من أهمها تدعيم هذه الكتب بالموضوعات المرتبطة بالأمن الوطني وتوحيد مفاهيم الأمن الوطني في هذه الكتب وتعزيزها بالقيم السلوكية المرتبطة بالأمن الوطني.
This study aimed at revealing the role of social studies and national textbooks in reinforcing national security in Saudi Arabia and the outlook of this role. Qurayyat Governorate is considered a model for this study. To achieve the objectives of the study, the researchers prepared a questionnaire that consisted of 33 items distributed under four domains. Nine questions were prepared for the interviews with the teachers in order to reveal the future role of social studies and national textbooks in reinforcing the national security in Qurayyart Governorate. The sample of the study consisted of 145 social studies teachers. They were selected using purposive sampling method. The results of the study showed that the role of Saudi social studies and national textbooks in reinforcing national security, from the point of view of teachers, scored a high degree in average and in all domains. Moreover, there were very few statistical differences in the views of the teachers regarding the role of social studies and national textbooks in reinforcing the national security, due to the variables of academic qualification and years of service. Furthermore, the results showed the future role of social studies and national textbooks in reinforcing national security incorporates different aspects, most importantly, reinforcing the curriculum with topics related to national security, unifying the definitions of national security in the textbooks, and promoting values and behavior that foster national security.
Keywords: السعودية -- المناهج التربوية -- الدراسات الاجتماعية -- التربية الوطنية -- الأمن الوطني